DNA damage in lens epithelium of cataract patients in vivo and ex vivo. (20th September 2012) - Osnes‐Ringen, Øyvind; Azqueta, Amaia O.; Moe, Morten C.; Zetterström, Charlotta; Røger, Magnus; Nicolaissen, Bjørn; Collins, Andrew R.
Abstract. Purpose: DNA damage has been described in the human cataractous lens epithelium, and oxidative stress generated by UV radiation and endogenous metabolic processes has been suggested to play a significant role in the pathogenesis of cataract. In this study, the aim was to explore the quality and relative quantity of DNA damage in lens epithelium of cataract patients in vivo and after incubation in a cell culture system. Methods: Capsulotomy specimens were analysed, before and after 1 week of ex vivo cultivation, using the comet assay to measure DNA strand breaks, oxidized purine and pyrimidine bases and UV‐induced cyclobutane pyrimidine dimers. Results: DNA strand breaks were barely detectable, oxidized pyrimidines and pyrimidine dimers were present at low levels, whereas there was a relatively high level of oxidized purines, which further increased after cultivation. Conclusion: The observed levels of oxidized purines in cataractous lens epithelium may support a theory consistent with light damage and oxidative stress as mediators of molecular damage to the human lens epithelium. Damage commonly associated with UV‐B irradiation was relatively low. The levels of oxidized purines increased further in a commonly used culture system. This is of interest considering the importance and versatility of ex vivo systems in studies exploring the pathogenesis of cataract.